Risk Assessment as a Tool for Mobile Plant Operators for Sustainable Development: Lessons from the Western Australian Mining Industry - Owais, Faiza (Curtin University, 2022)
Mobile plant is used extensively not only in the Western Australian (WA) Mining Industry but internationally as well. The use of mobile plant has inherently high risk and every year is associated with a significant number of workplace fatalities and injuries. Prior to this research being conducted there was no specific data published related to mobile plants incidents and fatalities for the Western Australian mining industries. The aim of this research was to improve the safety performance of mobile plant operators in the Western Australia (WA) mining industry by identifying the causes of mobile plant incidents reported to Resources Safety between 1/1/2007 and 31/3/2020.